Assessment Practices Among Early Childhood Educators in the TEMA West Metropolis, Ghana - Agbayisah, Seth; Dzakadzie, Yayra (Advances in Social Sciences Research Journal, 2025)
The study sought to investigate the assessment practices deployed by early childhood educators, establish the gender and professional qualification differences in the assessment practices of the educators and examine the challenges teachers encounter in the use of assessment practices in the Tema West Metropolis, Ghana. Two research questions and hypotheses guided the study. Descriptive survey design was used for the study. The instrument for data collection was a self-constructed 4-point Likert type scale questionnaire. The study covered 200 ECE teachers within 40 basic schools in the Tema West metropolis. Census technique was used to select the participants for the study. Descriptive statistics (mean and standard deviation) were used to analyze data obtained with respect to each research question. Populated T-Test analysis was also used to analyze the responses of the teachers with respect to each research question. Again, Independent sample T-test and One-Way ANOVA were used to test the hypothesis 1 and 2 respectively. It was evidenced from the study that the teachers in the Tema West Metropolis use of some formative assessment practices among which were, building of portfolio, the use of observation, informal conversation, self and peer assessment as well as performance-based assessment. Notwithstanding this, the teachers still engage in the use of formal or traditional assessment practices such as pencil and paper tests which is not healthy for the holistic development of children during their early years of education. Furthermore, while the assessment practices of teachers in the Tema West Metropolis are significantly the same across male and female categories, the assessment practices of teachers differ significantly across the teachers’ professional qualifications. Major challenges that confront ECE teachers in assessing children during their early years are inadequate indoor and outdoor resources for assessing children, lack of understanding of children’s assessment outcomes, overcrowding or large number of children among others. The study concludes therefore that although teacher in the Tema West Municipality use some formative assessment, there is still a high use of pen and paper test among the teachers. The study recommended that the teachers should be sensitized through series so professional development training and workshops on the negative effects of pen and paper tests on children to discourage them from using these traditional forms of assessment practices which do not help the holistic development of children, it is also recommended among others that the the educational directorate in the metropolis through the help of Ghana Education Service (GES) should identify other sources of funding like appealing to NGOs to help provide teaching and learning materials for teaching and assessing children in the metropolis.